Zarzou Beauty Skincare / Adam Izzat Azmi - Azmi, Adam Izzat (2021)
Assalamualaikum and hi, during making this business opportunity, I learnt a lot about how to manage business and how to control my income. It was best experience that turns me to be hardworking, supportive and dedicated person. I would like to say thank you to all my friends and my supportive lecturer because conduct me until I can finish my business opportunity. Firstly, I sold a skincare product branded from ZarZou Beauty Company. ZarZou Beauty have many types of skincare product that helps user to prevent breakout skin and give full protection to prevent acne such as Brightening Hydrating Serum to prevent pimples, repair dark spots and prevent inflammation. Repairing and Soothing Facial Serum that has their own function to help our skin become flawless and repair all of acne breakout. They also have face mist to give full protection and hydrating our skin all day. This is the product that have been chosen from all Malaysian people because the products were successful and the price is also reasonable and affordable. I would like to recommend this product to all people who have skin breakout and want to get rid of acne. The ingredients that they used is very expensive and have own function like Niacinamide to brighten the skin, Hyaluronic Acid to prevent acne and Vitamin C to repair scars. ZarZou Beauty was declared in 1st August 2019 by Zulaikha Rosli Founder of ZarZou Beauty. This product got attention and well known to all teenagers and workers. This company also hired dropship and I take part to be their dropship and I can get RM20 per product that I sold. During being a dropship, I got many experiences and learnt a lot in making business grow and I hope I can further my business to high level soon. Moreover, I learnt how to manage the customer, their behaviors, their complaint and is it they satisfied or not with my products. I also get feedback from them and all the feedback was good and they all satisfied with my products. I also learnt how to promote my products in all social media during this pandemic and I also do marketing to give chance to another people who would like to find side income below me. I also learnt how to give full cooperation on my business but never lack my studies as a student of UiTM. Last but not least, I will mention all of my business below and I hope I my explanation satisfy the requirements. I’ve reach total sales RM1k above.